TH1.1: A mixed-methods research tool for improving measurement and understanding of intra-household decision making - Mwakanyamale, Devis F.; John, Innocensia; Heckert, Jessica; Fischer, Gundula; Seymour, Greg; Feleke, Shiferaw; Ferguson, Nathaniel; Cole, Steven M. (International Institute of Tropical Agriculture, 2022)
A key aspect of women's empowerment is participation in important intra-household decisions. This paper describes a new mixed-methods emic-informed approach that we developed involving multiple stakeholders to explore intra-household decision making on agriculture- and expenditure-related matters. The tool was piloted in cassava-producing districts in Kagera and Kigoma Regions of Tanzania. It first comprises a qualitative guide that was used to interview 40 dyads (mostly married couples) who grow, process, and/or trade cassava. We conducted thematic content analysis of these interviews and identified seven distinct patterns that dyads used to make decisions. These included: husband shares idea, discusses with wife, then (i) husband makes the final decision; (ii) wife makes the final decision; or (iii) they make a joint final decision. Alternatively, (iv) husband shares idea with his wife before he makes the final decision; or wife shares idea, discusses with husband, then (v) husband makes the final decision; (vi) wife makes the final decision; or (vii) they make a joint final decision. These patterns informed the development of vignettes that describe intra-household decision making, along with survey questions asking respondents which decision-making vignettes they most identify with and additional questions on why and how decisions are made in their households. Finally, these new modules were included in a multi-topic survey that was administered to around 1300 couples to validate the new decision-making modules. Our approach aims to help us better measure and understand intra-household decision making and its links to household-level economic, food, and nutrition security outcomes.